SPEECH COMPETENCE OF FUTURE SPECIALISTS IN DOCUMENTARY STUDIES: PEDAGOGICAL CONDITIONS - Сёмина, Анастасия (SWorldJournal, 2022)
The article considers the problem of insufficient speech competence of specialists in document science. Definitions of language personality and characteristics of competent speech of future bachelors in document science are described. Interdisciplinary co